Consumer Behavior toward Organic Food Products: A Study from Udaipur, India - , Lokesh Gupta; , Vinod Kumar; , Kamla Mahajani; , Amit Kumar; , Nikita Wadhawan (Archives of Current Research International, 2025)
The growing awareness of health and environmental sustainability has increased interest in organic food consumption. This study was conducted in Udaipur to analyse consumer behaviour towards organic food products. One hundred respondents were randomly selected from various colleges of MPUAT, Udaipur, Rajasthan, and data were collected through a structured Google Form based on a modified, tailor-made questionnaire. The study employed descriptive statistical tools, including Mean, Standard Deviation (SD), Mean Per Score (MPS), and ranking. The findings revealed a high level of awareness regarding organic food products, with 92% of respondents reporting familiarity. Health benefits, environmental concerns, and quality assurance influenced purchase behaviour. Most respondents (86%) purchased organic products, particularly vegetables, grains, and fruits, with local stores and farmers' markets being the most common sources. However, price sensitivity and availability were significant concerns. While many were willing to pay a premium for organic products, a substantial number also expressed that such purchases affected their family budgets. The independent variables like level of education, number of family members and Monthly income were positively significant, and occupation was negatively significant. The study concludes that while there is a strong awareness and positive perception of organic products among the student population, affordability and accessibility remain barriers to broader adoption. Strategic awareness campaigns and policy interventions could further promote organic food consumption. The finding implies the need for strategic awareness campaigns, improvement in supply chain and policies related to organic food so that organic food become more affordable and accessible. Future research could explore impacts of awareness programme, consumer trust in certification of organic products to bridge the gaps.